Si Dieu Ètait tout un chacun de nous? - Kingue, Samuel Ebelle (Langaa RPCIG, 2008)
If Each One Of Us Would Be God? Is a hypothesis that rejects the logic of religious institutions with their ability to limit the evolution of human consciousness, since the reality of our existence within religions is defined as fixed. If each one of us would be God, we would return into the deepness of our absolute consciousness and be in contact with our true selves. This challenging statement awakens the conscious deadening of a Supreme human being, as the search for our spiritual identity has nothing to do with the collective degree that is dictated by religious rules, which creates depend.